Bibliometric analysis of hydrogels in bone regeneration: Research trends and future perspectives - Alimujiang Abudourousuli; Aikebaierjiang Aisaiti; Kan Jiang; Shalayiding Aierxiding; Kutiluke Shoukeer; Ran Han; Aikeremujiang Muheremu (Regenerative Therapy)
Objective: To analyze the research status and development prospects of hydrogels in the field of bone regeneration based on bibliometric methods. Methods: In the Web of Science Core Collection database, a total of 1382 representative articles related to the application of hydrogels in bone regeneration were selected as of the end of 2023. Utilizing the tools VOSviewer and CiteSpace, an in-depth bibliometric visualization analysis was conducted to reveal the countries, authors, core literature, and journals that are highly productive in this field. Additionally, the research trends and development prospects within this area were analyzed. Results: This study uses VOSviewer and CiteSpace to analyze 1382 highly cited articles on bone regeneration and materials science, revealing key trends and the evolution of the field. The United States, China, South Korea, Germany, the UK, and Japan are the leading countries in scientific output, with strong collaboration networks. Major research institutions, particularly in China and Japan, focus on hydrogels for bone regeneration. Top journals include International Journal of Biological Macromolecules and Acta Biomaterialia. Key authors include Timothy E. L. Douglas, known for developing mineralization-enhanced hydrogels, and Robert E. Guldberg, focused on growth factor delivery systems. The field has shifted from simple filling materials to multifunctional composites, with advancements in gene editing, signaling molecules, and bone regeneration drugs. Future trends include smart hydrogels, 3D printing, bioactive factor integration, cell engineering, and optimizing biodegradability and biocompatibility. Multifunctional composite hydrogels are expected to become the go-to materials for clinical bone repair. Conclusion: Advancements in technology have transformed hydrogels from simple fillers to multifunctional composites, playing a crucial role in bone regeneration. Future trends include smart hydrogels, 3D printing, bioactive factor integration, cell engineering, and optimized biodegradability and biocompatibility. These developments indicate hydrogels will become the preferred material for clinical bone defect repair, significantly enhancing bone tissue repair and regeneration.